2013
DOI: 10.2903/j.efsa.2013.3264
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the public health hazards to be covered by inspection of meat from farmed game

Abstract: Salmonella spp. in farmed wild boar and Toxoplasma gondii in farmed deer and farmed wild boar were ranked as a high priority for meat inspection. Trichinella spp. in wild boar was ranked as low priority due to current controls, which should be continued. For chemical hazards, all substances were ranked as medium or lower potential concern. More effective control of biological hazards could be achieved using an integrated farm to chilled carcass approach, including improved food chain information (FCI) and risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 217 publications
0
24
0
Order By: Relevance
“…It is related to the mandate from the Commission for a scientific opinion on the public health hazards to be covered by inspection of meat. The scientific opinion on the public health hazards to be covered by inspection of meat from farmed game (EFSA BIOHAZ Panel, 2013a) and this report under this mandate concern the meat inspection of farmed game and they were published in June 2013.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is related to the mandate from the Commission for a scientific opinion on the public health hazards to be covered by inspection of meat. The scientific opinion on the public health hazards to be covered by inspection of meat from farmed game (EFSA BIOHAZ Panel, 2013a) and this report under this mandate concern the meat inspection of farmed game and they were published in June 2013.…”
Section: Discussionmentioning
confidence: 99%
“…In general, very little information is available on farmed wild boar populations in the EU (EFSA, 2012;EFSA BIOHAZ Panel, 2013a). The BIOMO questionnaire survey revealed that the number of holdings of farmed wild boar in countries is small and each holding usually has fewer than 30 animals per holding.…”
Section: Farmed Wild Boarmentioning
confidence: 99%
See 3 more Smart Citations